Fabrication and in vitro biological evaluation of photopolymerisable hydroxyapatite hydrogel composites for bone regeneration. (April 2014) - Killion, John A; Geever, Luke M; Devine, Declan M; Higginbotham, Clement L
The aim of this study was to improve the bioactive and compressive properties of photopolymerisable polyethylene glycol hydrogels with the incorporation of hydroxyapatite at different loadings. The synthesis of pure hydroxyapatite was verified through Fourier transform infrared spectroscopy (FTIR) analysis by the complete reaction of all constituents. The formation of a bioactive layer of the hydrogel based composites was confirmed through the formation of carbonate hydroxyapatite after soaking the samples in simulated body fluid. The incorporation of hydroxyapatite into the system resulted in an increase in Young's modulus from 4.36 to 12.73 MPa and an increase in the stress at limit value from 1.20 to 4.42 MPa. This was due to the hydroxyapatite absorbing the compressive load, the polymer matrix distributing the load, a reduction in swelling and the presence of physical crosslinking between both components. Drug dissolution testing showed that the release rate of a drug from the hydrogels was dependent on the molecular weight of the polymer and the type of drug used.